2015
DOI: 10.3168/jds.2014-7992
|View full text |Cite
|
Sign up to set email alerts
|

Colostrum composition of Santa Inês sheep and passive transfer of immunity to lambs

Abstract: This study aimed to analyze the chemical composition and the IgG concentration of the colostrum, transitional milk, and mature milk of Santa Inês ewes as well as the transfer of passive immunity to lambs. Thirty-two pregnant ewes and 38 lambs were used. Ewes were milked immediately after lambing and at 12, 24, 36 h and 10 d postpartum. Colostrum was provided to the lambs at 40±15 min (mean±SE) after birth and then at 30-min intervals for obtaining the intake closest to 10% of body weight, and transitional milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
45
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 38 publications
10
45
2
2
Order By: Relevance
“…Moreover, forage availability is at its minimum level: most sheep are underfed and in a poor body condition. In this physiological status, the immunized system of sheep does not operate correctly, with a low globulin rate and a reduced immunized response to the vaccine [6972]. In addition, sheep are left straying freely and they need to be gathered for the vaccination, which is a cumbersome work for the farmers at this period.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, forage availability is at its minimum level: most sheep are underfed and in a poor body condition. In this physiological status, the immunized system of sheep does not operate correctly, with a low globulin rate and a reduced immunized response to the vaccine [6972]. In addition, sheep are left straying freely and they need to be gathered for the vaccination, which is a cumbersome work for the farmers at this period.…”
Section: Discussionmentioning
confidence: 99%
“…Jalilian and Moeini (2013) also stated that colostrum production (10 and 18 h postpartum) of ewes with BCS of 3 was higher than ewes with BCS of 2, 2.5 and ≥ 3.5 (P < 0.05). However, BCS of ewe at lambing had no effect on colostrum IgG concentration (Al-Sabbagh et al, 1995;Boucher, 2014;Alves et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In Santa Inês ewes, Alves et al (2015) reported 16.97% total solids, 5.77% fat, and 5.39% protein at the 10th day postpartum. Moreover, in contrast to cow milk, sheep milk is composed of fat globules that have a higher surface to enzymatic activity due to the reduced size and higher triglyceride percentage, which allows easier digestion.…”
Section: Discussionmentioning
confidence: 99%